Personalizacija v virtualnem učnem okolju Moodle - Batič, Boštjan (Organizacija znanja, 2024)
The education system should provide an inclusive learning environment where every individual is important and entitled to equal opportunities. This paper presents the activities and functionalities of the Moodle virtual learning environment based on the case study of the e-classroom where the potential for providing an inclusive learning environment based on the idea of personalised learning was analysed. When delivering e-learning courses in Moodle, the tools and activities were analysed according to the following criteria: a) enabling active content creation, b) supporting different learning styles (creating different materials according to learning style), c) enabling planning of the course according to the learner's interest, d) enabling communication between learners and providers, and e) enabling ongoing checking of progress or knowledge. The analysis showed that the Moodle installation used by Arnes Classrooms provides 18 activities that can support personalised learning. Based on different learning styles, this is enabled by 17 activities, online checking of knowledge and progress is enabled by 6 activities, active content creation is enabled by 6 activities, and educational planning and personal interests are supported by 24 activities or functionalities. Arnes Classrooms contain 8 activities that allow communication or networking between participants. Seven functionalities are available in Arnes Classrooms to successfully plan the implementation of personalised learning. From the results it can be concluded that the tools in Moodle allow personalisation of learning, which is important for further development of training and the development of tools to improve the quality of learning experience in this virtual learning environment.
Keywords: e-izobraževanje; e-learning; inclusive education; inkluzivno izobraževanje; Moodle; personalized learning; personalizirano učenje; virtual learning environment; virtualna učna okolja